Continuous optical chlorophyll-a and turbidity data along R/V SONNE cruise SO300/1 - Julia Oelker; Udo Barckhausen; Prithivi Dass Bissessur; Daniela Voß; Jochen Wollschläger (PANGAEA, 2025)
Underway optical chlorophyll-a and turbidity data were collected along the cruise track with Sea-Bird Scientific ECO FLNTU sensors installed within two autonomous measurement systems, called self-cleaning monitoring boxes (SMBs). The SMBs measure alternatingly. While one box is measuring, the other one is being cleaned. The boxes switched generally every 6 hours. The water inlet for the SMBs is at about 4 m below sea surface. Observed chlorophyll-a and turbidity data were both quality controlled. Analysis of the chlorophyll-a data during parallel operation of the sensors in the two boxes showed a significant offset between the sensors. The sensors were aligned resulting in a consistent chlorophyll-a time series. A comparison for the corrected chlorophyll-a with satellite data using the GlobColour CHL1 product is additionally provided. The Pearson correlation coefficient is low due to the overall small parameter range. Most data points lie at the 1:1 line within their measurement uncertainty. Details on all quality control steps and the comparison with satellite data can be found in the data processing report. Note that the instruments are factory-calibrated, however, no post-calibration was performed due to missing reference data. The resulting data set contains the original data and corresponding quality flags achieved by the quality control algorithm, and, in case of chlorophyll-a, also the corrected data with corresponding quality flag. The data source is given through the name of the active SMB. The data set contains data during transit time and station work. We recommend to use ship extquotesingles speed to filter for only transit data.